A study of a calibration technique for a newly developed thyroid monitor and its uncertainties due to body size for radioiodine measurements. (April 2020) - Yoshitomi, H.; Nishino, S.; Tanimura, Y.; Takahashi, M.
Abstract: We have developed a portable thyroid monitoring system to measure thyroid doses for members of the public in a nuclear emergency. It is assumed that a large number of these monitoring systems are deployed and maintained for emergency situations. Hence, the calibration performed should be performed as simple as possible. We proposed a new calibration method based on standard voxel phantoms using a point source. By applying this method to the thyroid monitoring system, the counting efficiencies were evaluated. Although this monitor is properly calibrated, any differences between the phantoms used in the calibration and the monitored subjects can affect the measurement accuracy. Therefore, the influence of the anatomical features of the subjects on the detection efficiencies was investigated in detail by Monte Carlo calculations. The effects of the body size on the counting efficiencies of the thyroid monitoring system were estimated using several voxel phantoms. Consequently, the uncertainties in the counting efficiencies due to the body size were found to be within 25%. Highlights: A calibration method for a thyroid monitor using a point source based on voxel phantom was proposed. The counting efficiencies of our newly developed thyroid monitoring system were determined by applying this new method. The uncertainty due to the body size was estimated to be 25 % at a maximum by using calculations with various voxel phantoms.